Teamwork cross-culturally: Christ-centered solutions for leading multinational teams - Lingenfelter, Sherwood G. (Baker Academic, a division of Baker Publishing Group, 2022)
"Intercultural ministry leaders cast a vision for how teams made up of diverse peoples can serve in unity as the body of Christ despite the complicated problems that arise, doing the work of ministry around the world in ways that honor God"--